Regulatory T Cells Show Dynamic Behavior During Late Pregnancy, Delivery, and the Postpartum Period - Lima, J (2019)
Regulatory T cells (Tregs) are critical immunomodulators during early pregnancy by preventing maternal T-cell activation against fetal cells. However, how populations of maternal Tregs vary during and after pregnancy in humans is still unclear. Therefore, we investigated Treg subsets in the peripheral blood of pregnant women from late pregnancy through the postpartum period. To accomplish this, the following circulating Treg subsets were analyzed in 43 healthy pregnant women and 35 nonpregnant women by flow cytometry during the third trimester, on the day of delivery, and postpartum: CD4DimCD25Hi, CD4+CD25HiFoxp3+, and CD4+CD25HiCD127-/dim. Additionally, the expression levels of the transcription factor Foxp3 in CD4DimCD25Hi Treg were analyzed. We have found that CD4DimCD25Hi Treg subset significantly decreased in the pregnant women on the day of delivery relative to the third trimester ( P < .05), and that all Treg subsets significantly increased postpartum compared to the third trimester and the day of delivery ( P < .05). Moreover, the Foxp3 expression ratios within the CD4DimCD25Hi Treg subset decreased during pregnancy and until delivery compared to those measured in the nonpregnant women and significantly increased postpartum compared to the third trimester and the day of delivery ( P < .05). Thus, despite their established role in offering immunoprotection to the fetus in early pregnancy, the number of circulating Tregs also varies from late pregnancy to the postpartum period. Our results offer an explanation for the possible effects of pregnancy on the clinical outcomes of some autoimmune diseases during the postpartum period.